Leveraging Design Discipline to Empower Innovative Cultural Tourism in Dalian: A Study on Teaching Strategies in the Fundamentals of Image Production Course - Sun, Xiaolei (Journal of Educational Research and Policies, 2026)
Against the backdrop of the integration of culture and tourism, the high-quality development of the cultural tourism industry demands a new caliber of creative talent. As a critical field connecting cultural expression with communication media, the design discipline holds significant potential for boosting local cultural tourism. Taking the core Visual Communication Design course, Fundamentals of Image Production, as a case study, this paper explores innovative teaching strategies that deeply combine academic instruction with local cultural tourism practices, specifically tailored to Dalian's regional culture and industrial needs. Employing a mixed-method approach comprising literature review, case studies, action research, and surveys and interviews, etc, the study constructs an integrated "Curriculum Content–Cultural Tourism Theme–Image Practice" teaching model, which was subsequently validated through practical implementation. The findings indicate that this model not only enhances students' capabilities in image creation, fostering their innovative consciousness, but also deepens their understanding of indigenous culture. But it also provides effective support for content production and promotion in local cultural tourism. Consequently, this research offers valuable implications for how design disciplines can better serve regional economic and cultural development.